2022
DOI: 10.3390/w14162486
|View full text |Cite
|
Sign up to set email alerts
|

Failure Analysis and Treatments of Tunnel Entrance Collapse Due to Sustained Rainfall: A Case Study

Abstract: Rainfall is a crucial issue affecting the entrance slope stability of mountain tunnels, as it decreases the shearing strength of soil and reduces the stability of tunnel entrance. This paper presents a case history of the collapse failure of a tunnel entrance in Yunnan Province under rainfall conditions, in which the failure mechanism and potential factors and treatment measures were discussed by field investigation, theoretical analysis, and in-situ monitoring. The analysis results show that the decrease of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The analysis results indicated that the reduction in soil shear strength was primarily due to a decline in the matric suction value caused by an increase in soil water content, leading to decreased sliding resistance in the entrance slope and ultimately triggering the collapse. Floodwaters can infiltrate the surrounding rock at the tunnel entrance can lead to erosion and softening of the material, which are the main causes of tunnel collapse (Yang et al, 2018;Wang and Cheng, 2021;Chen et al, 2022).…”
Section: Tunnelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis results indicated that the reduction in soil shear strength was primarily due to a decline in the matric suction value caused by an increase in soil water content, leading to decreased sliding resistance in the entrance slope and ultimately triggering the collapse. Floodwaters can infiltrate the surrounding rock at the tunnel entrance can lead to erosion and softening of the material, which are the main causes of tunnel collapse (Yang et al, 2018;Wang and Cheng, 2021;Chen et al, 2022).…”
Section: Tunnelsmentioning
confidence: 99%
“…Lyu et al, 2018 used analytic hierarchy process (AHP) and the interval AHP (I-AHP) methods to evaluate regional flood risk, emphasizing the vulnerability of metro systems. Among the various factors contributing to the collapse of the tunnel entrance section, rainfall emerges as a significant factor, with a majority of tunnel collapse incidents attributed to rainfall (Chen et al, 2022).…”
Section: Tunnelsmentioning
confidence: 99%
“…Due to the poor geological conditions, severe weathering of the rock, complex topography, and the disturbance of the tunnel construction, the tunnel entrance section is prone to deformation and instability of the tunnel slope, resulting in geological damage, such as landslides and collapses, which are commonplace for tunnel construction accidents. As a result, there is a wealth of research related to the entrance section of tunnels, such as structural damage to the lining of the entrance section [30], risk assessment of the entrance section using neural networks [31], the interaction between the cavern envelope and the lining under seismic action [32], location of seismic weak points in the cavern section [33], the establishment of a three-dimensional dynamic construction model of the cavern section combined with monitoring and measurement to analyze the extent of its deformation [34], the effect of rainfall on the slope stability of the cavern, and the impact of rainfall on the slope stability of the cave entrance section [35]. The results of Hou et al [36] showed that the combined effect of excavation and rainfall led to damage to the foot of the tunnel slope, which, in turn, led to slope instability as the extent of the damage expanded.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the diversity, regionality, seasonality, and other characteristics of tourism resources, in order to better tap the characteristics of various tourism resources, further enhance the attraction of tourism resources, and protect them while reusing them, it is necessary to make scientific and reasonable planning of tourism resources to realize the sustainable utilization of tourism resources, the effective development of tourism destinations, and the three benefits of tourism industry [20][21][22]. Tourism planning refers to the full excavation and protection of tourism resources and the rational planning and layout of tourism destinations based on the scientific evaluation of tourism resources; the characteristics of tourism resources and the natural, social, and economic environment of tourism destinations; and the use of planning ideas [23][24][25].…”
Section: Introductionmentioning
confidence: 99%